Influence of Reaction Time and Hydrochloric Acid Volume on Rutile Titanum Dioxide Nanorods Thin Film - Ahmad Norazlina; Talib Azman; Mohamad Fariza; Ahmad Mohd Khairul; Kusnanto Mukti Wibowo (Proceedings Series on Health & Medical Sciences, 2021)
Titanium dioxide (TiO2) nanostructured materials have attracted attention due to their application at various fields such as photocatalysis, solar cell and photochemical applications. Whereas TiO2 could exhibit high efficiency of solar cell and economical than traditional silicon solar cells. In this study, hydrothermal method demonstrated to synthesis TiO2 nanorods properties at different hydrothermal reaction times and various hydrochloric acid volumes. Increasing the reaction time could influence the thickness towards high crystalline rutile formation while modifying the hydrochloric (HCl) acid concentration favours a great influence on the morphologies and alignment of the nanostructure. The result is beneficial for improvements thin film power conversion efficiency.